Concept of employee discipline and Z N Consultants leave attendance policy: A case study in Z N Consultants - Yasmin, Nishat (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.